Kabes Pupphy Learning Media (Pythagorean Proving Puzzle) for Mathematics Learning Pythagorean Material - Abdur Rahman Mustafa; Dzuwi Nafida Hasan; Erna Zeniatul Baiti Albahria; Indah Nur Komala Sari; Risqa Atica Sari; Muhammad Khoiril Akhyar; Agus Surur; Hasnah Binti Mohamed; Hat?ra Günerhan (Journal International Inspire Education Technology, 2022)
This study aims to describe learning media to facilitate students in constructing an understanding of the Pythagorean theorem. This study describes a learning media product in the form of a puzzle called Pupphy (Pythagorean Proving Puzzle). Pupphy is a puzzle proving the Pythagorean theorem on the Pythagorean theorem material for grade VIII students in junior high school. This media is different from the others because it is made from environmentally friendly materials that are easily found in the surrounding environment and can also be made by students themselves. This research uses a qualitative approach that uses narrative data and aims to describe a medium that can be used in learning mathematics using Pythagorean material as an innovative learning method. Pupphy is packaged in an interactive animation form that is equipped with an evaluation of the understanding of the Pythagorean theorem so that it allows students to carry out individual evaluations of competency achievements related to the Pythagorean theorem. The structure of the material in Pupphy consists of an explanation of the elements of a right triangle, an animation of the discovery of the Pythagorean theorem formula, and the application of this formula to right triangles. to find out the feasibility of a test conducted by media experts and material experts and also conducted on students.